2018
DOI: 10.1111/1467-8268.12336
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Price Transmission and Rent‐seeking in Road Fuel Markets: A Comparative Study of South Africa and Selected Eurozone Countries

Abstract: This paper presents the first-ever analysis of South African and Eurozone road fuel markets for the possibility that firms may be manipulating the tax system to conceal rent-seeking behavior using the nonlinear ARDL model recently advanced by Shin et al. (2013). The paper also examines these markets for asymmetric price adjustment following changes in crude oil costs in the aftermath of the 2007-2008 Global Financial Crisis. Monthly data for gasoline, automotive diesel and costs of imported crude oil from Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
(48 reference statements)
4
16
1
Order By: Relevance
“…These facts indicate that the demand for non-road fuels is generally more elastic compared to the demand for road fuels such that in economic terms, there should be more likelihood of rent-seeking and asymmetric price adjustment in the markets for road fuels. This categorization of retail petroleum products into road fuels and non-road fuels is consistent with the existing literature, including Greenwood-Nimmo and Shin [21] and Ogbuabor et al [2] . For the eight countries included in this study, Organisation for Economic Co-operation and Development (OECD) [52] conducted a country by country evaluation and found that price elasticity in their road fuel markets is generally low due to some structural factors, such as frequent and relatively small transactions with a fragmented demand side, high barriers to entry, symmetry between leading suppliers due to the vertical relations and nationwide presence of the companies (especially in Italy, Germany, and Spain, where dominant firms are quite visible in the downstream petroleum markets), and difficulties in setting up retail outlets and securing supplies of road fuels, among others.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…These facts indicate that the demand for non-road fuels is generally more elastic compared to the demand for road fuels such that in economic terms, there should be more likelihood of rent-seeking and asymmetric price adjustment in the markets for road fuels. This categorization of retail petroleum products into road fuels and non-road fuels is consistent with the existing literature, including Greenwood-Nimmo and Shin [21] and Ogbuabor et al [2] . For the eight countries included in this study, Organisation for Economic Co-operation and Development (OECD) [52] conducted a country by country evaluation and found that price elasticity in their road fuel markets is generally low due to some structural factors, such as frequent and relatively small transactions with a fragmented demand side, high barriers to entry, symmetry between leading suppliers due to the vertical relations and nationwide presence of the companies (especially in Italy, Germany, and Spain, where dominant firms are quite visible in the downstream petroleum markets), and difficulties in setting up retail outlets and securing supplies of road fuels, among others.…”
Section: Introductionsupporting
confidence: 88%
“…Studies such as Borenstein et al [14] , Lee [54] , and Bachmeier and Griffin [32] , among others, give credence to this. More recent studies like Greenwood-Nimmo and Shin [21] and Ogbuabor et al [2] also applied this framework in modeling asymmetric price adjustments across various retail energy markets. The method is fundamentally an extension (in an asymmetric manner) of the linear ARDL framework for modeling equilibrium relationships initially advanced by Pesaran et al [55] (henceforth PSS).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations